The Relationship Level of Knowledge and Community Attitude and Behavior Towards the Prevention of the Covid-19 Pandemic in the Working Area of the Pasar Merah Health Center - Zuhra Fauzia; Zaim Anshari; Anna Yusria; Aulia (PT Inovasi Pratama Internasional, 2023)
The rapid spread of the virus and the ever-increasing incidence of COVID-19 must be stopped immediately with specific prevention and treatment. Communities have a big role in preventing COVID-19. Good knowledge and a positive attitude and behavior in preventing COVID-19 can be an effort to stop the transmission of COVID-19. This research was conducted to determine the relationship between the level of knowledge and attitudes and behavior of the community towards the prevention of COVID-19 in the working area of the Pasar Merah Health Center. This research is analytic observational with a cross-sectional study design. The number of research samples was 100 people who were taken using the simple random sampling method and the data was taken through a questionnaire which was immediately filled in, so that the data collected was primary data. Bivariate analysis using somers'd test. Of the 100 samples, it shows that as many as 88% of the people at the Pasar Merah Health Center have good knowledge, 93% have good attitudes, and 80% have good behavior. The results of the bivariate test using the somers'd correlation test between the level of knowledge and attitudes obtained p value = 0.003 (<0.05). The results of the correlation test between the level of knowledge and behavior obtained p value = 0.001 (<0.05). Based on the results of this study, it can be seen that there is a significant relationship between knowledge and attitudes and behavior of the community towards preventing the COVID-19 pandemic in the working area of the Pasar Merah Health Center.